Profil Berpikir Kreatif Mahasiswa dalam Memecahkan Masalah Mawaris Tipe Investigasi Matematika Ditinjau dari Perbedaan Gender - Rini Agustini; Jumaita Nopriani Lubis; Herman Pelangi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This type of research is descriptive qualitative, which is to describe the creative thinking profile of students in solving mawaris problems in the type of mathematical investigation in terms of gender differences. This research was conducted at IAIN Padangsidimpuan. Sources of data used in this study are primary data sources, namely students majoring in Ahwalu As-Syakhsiyah at IAIN Padangsdimpuan, amounting to 6 people, namely 3 male subjects and 3 female subjects and secondary data sources, namely lecturers who teach the subject of fiqih mawaris in the department. Ahwalu As- Syakhsiyah at IAIN Padangsdimpuan. The data collection instruments used in this study were tests, observation and documentation. The creative thinking test is in the form of questions related to the material of fiqh mawaris which consists of 6 questions. The trial results showed that male subjects' creative thinking was superior to the elaboration indicator (detail) by 80.5%, belonging to the high category while female subjects on the elaboration indicator (69.67%) belonged to the medium category. The trial results showed the details of the answers given by male and female subjects. The ability to think creatively for male subjects and female subjects on three indicators, namely indicators of fluency, flexibility and originality are classified in the low category.